2022
DOI: 10.1155/2022/8071406
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances and the Mechanism of Astaxanthin in Ophthalmological Diseases

Abstract: Astaxanthin (AST) is a naturally occurring carotenoid that has strong antioxidant, anti-inflammatory, and antiapoptosis effects and is used for the prevention of cancer. There is growing evidence that AST has multiple protective effects against various eye diseases. This article reviews the function and the potential mechanism of AST in dry eye syndrome, keratitis, cataract, diabetic retinopathy, age-related macular degeneration, high intraocular pressure, and other ocular diseases. It provides a theoretical b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…Astaxanthin is a natural carotenoid. Previous studies suggested that astaxanthin might have the potential to reduce the IOP, which was attributed to its potent antioxidant capacity [31]. It can alleviate protein oxidation, lipid peroxidation, and apoptosis caused by elevated IOP, thereby inhibiting apoptosis of retinal ganglion cells and protecting the retinal integrity from damage due to high IOP [32].…”
Section: Discussionmentioning
confidence: 99%
“…Astaxanthin is a natural carotenoid. Previous studies suggested that astaxanthin might have the potential to reduce the IOP, which was attributed to its potent antioxidant capacity [31]. It can alleviate protein oxidation, lipid peroxidation, and apoptosis caused by elevated IOP, thereby inhibiting apoptosis of retinal ganglion cells and protecting the retinal integrity from damage due to high IOP [32].…”
Section: Discussionmentioning
confidence: 99%
“…They are predisposed to chronic oxidative stress due to their high level of oxygen consumption and exposure to continuous light stimuli. As one aspect, it is suggested that ROS-induced DNA damage in RPE cells can contribute to the development of AMD, but studies also revealed increased ROS production in RPE cells from AMD patients due to the lost ability to increase superoxide dismutase (SOD) expression during oxidative stress [98]. High ROS levels and weakened cellular defense systems result in injury to the photoreceptors and subsequent apoptosis [97].…”
Section: Age-related Macular Degeneration and Carotenoidsmentioning
confidence: 99%
“…They can have convulsions mainly in the period when they lose blood. The loss of blood can generate more energy deficiency causing the formation of internal Fire leading to the formation of internal Wind generating convulsions [29]. They can have any type of tumor in the central nervous system, be it benign or malignant in nature, but have a basic cause that led to the formation of this lack of energy in these five massive internal organs.…”
Section: Introductionmentioning
confidence: 99%
“…Female patients who took the vaccine may have an even greater change in menstrual flow when they received the COVID-19 vaccine, increasing the flow, and it often does not improve when using hormonal medications or even sometimes worsens the patient's condition. The reason for this is that the use of hormones in this situation causes an even greater reduction in the patient's energy and creates more internal Heat, responsible for altered menstrual bleeding [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%